How to develop teaching material of buffer solution based on SETS? - D P Astuti; S Anwar (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This study aims to develop teaching materials for the buffer solution based onScience, Environment, Technology, and Society (SETS)to improve the science process skills.The research method used is development research, while the method of development ofteaching materials used is 4S-TMD. This article is the first part of the development of teachingmaterials that includes selection and structurization steps. In the selection step, developing theindicator accordance with the curriculum requirements, explaining the buffer conceptusingstandardized textbook sources, and analyzing SETS that can be integrated with the bufferconcept. In the structurization step was developed concept maps, macrostructures and multiplerepresentations that connect between the level representations of macroscopic, submicroscopic,and symbolic. The results of the selection and structurization steps were evaluated by expertlecturers. The results show that the teaching materials developed are in accordance with thecurriculum requirements, it has been ensured the scientific truth, the phenomena presented inaccordance withSETS and concept maps, macrostructures, and multiple representationsdeveloped have been valid. The first part of the development of teaching materials that includesthe selection and structurization steps results in a draft of teaching material for the buffersolution based on SETS.